Rat bone marrow mesenchymal stem cells induced by rrPDGF-BB promotes bone regeneration during distraction osteogenesis - Wu, Shuo; Zhang, Lijie; Zhang, Ruidan; Yang, Kang; Wei, Qin; Jia, Qiyu; Guo, Jian; Ma, Chuang (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Background: In the clinical treatment of large bone defects, distraction osteogenesis can be used. However, some patients may suffer from poor bone regeneration, or even delayed healing or nonunion. Problems with the aggregation and proliferation of primary osteoblasts, or problems with the differentiation of primary osteoblasts will lead to poor bone regeneration. Therefore, supplementing exogenous primary osteoblasts and growth factors when using distraction osteogenesis may be a treatment plan with great potential. Methods: BMSCs were extracted from rats and cultured. Subsequently, rrPDGF-BB was used to induce BMSCs. At the same time, male adult rats were selected to make the right femoral distraction osteogenesis model. During the mineralization period, phosphate buffer salt solution (control group), non-induction BMSCs (group 1) and rrPDGF-BB intervened BMSCs (group 2) were injected into the distraction areas of each group. Then, the experimental results were evaluated with imaging and histology. Statistical analysis of the data showed that the difference was statistically significant if P<0.05. Results: After intervention with rrPDGF-BB on BMSCs, the cell morphology changed into a thin strip. After the cells were injected in the mineralization period, the samples showed that the callus in group 2 had greater hardness and the color close to the normal bone tissue; X-ray examination showed that there were more new callus in the distraction space of group 2; Micro-CT examination showed that there were more new bone tissues in group 2; Micro-CT data at week 8 showed that the tissue volume, bone volume, percent bone volume, bone trabecular thickness, bone trabecular number and bone mineral density in group 2 were the largest, and the bone trabecular separation in group 2 was the smallest. There was a statistical difference between the groups (P<0.05); HE staining confirmed that group 2 formed more blood vessels and chondrocytes earlier than the control group. At 8 weeks, the bone marrow cavity of group 2 was obvious, and some of them had been fused. Conclusion: The study confirmed that injecting rrPDGF-BB into the distraction space of rats can promote the formation of new bone in the distraction area and promote the healing of distraction osteogenesis.